Knowledge and Skill Retention of In-Service versus Preservice Nursing Professionals following an Informal Training Program in Pediatric Cardiopulmonary Resuscitation: A Repeated-Measures Quasiexperimental Study. (22nd July 2013) - Sankar, Jhuma; Vijayakanthi, Nandini; Sankar, M. Jeeva; Dubey, Nandkishore
Abstract : Our objective was to compare the impact of a training program in pediatric cardiopulmonary resuscitation (CPR) on the knowledge and skills of in-service and preservice nurses at prespecified time points. This repeated-measures quasiexperimental study was conducted in the pediatric emergency and ICU of a tertiary care teaching hospital between January and March 2011. We assessed the baseline knowledge and skills of nursing staff (in-service nurses) and final year undergraduate nursing students (preservice nurses) using a validated questionnaire and a skill checklist, respectively. The participants were then trained on pediatric CPR using standard guidelines. The knowledge and skills were reassessed immediately after training and at 6 weeks after training. A total of 74 participants—28 in-service and 46 preservice professionals—were enrolled. At initial assessment, in-service nurses were found to have insignificant higher mean knowledge scores (6.6 versus 5.8, P = 0.08 ) while the preservice nurses had significantly higher skill scores (6.5 versus 3.2, P < 0.001 ). Immediately after training, the scores improved in both groups. At 6 weeks however, we observed a nonuniform decline in performance in both groups—in-service nurses performing better in knowledge test (10.5 versus 9.1, P = 0.01 ) and the preservice nurses performing better in skill test (9.8 versus 7.4, P < 0.001 ). Thus, knowledge and skills of in-service and preservice nurses in pediatric CPR improved with training. In comparison to preservice nurses, the in-service nurses seemed to retain knowledge better with time than skills.